The role played by civil society organizations in the 31 July 2013 harmonised elections in Zimbabwe: a case study of ZimRights - Tapera, Tichaona M. (Midlands State University, 2017)
The research sought to analyze the role played by CSOs with specific reference to ZimRights a grassroots based organization in the harmonized elections of 31 July in Zimbabwe. The main problem has been that the role of CSOs in elections has been down played and to some extent CSOs has been labeled as regime change agents and allies of opposition parties. A review of related literature was carried out to establish what other renowned scholars and authors had to say no the role CSOs play in elections. The researcher used qualitative method to analyze and present data in the research in order to obtain a critical analysis in the topic in question. The study established that CSOs played a significant role in the harmonized elections of July 31 2013 in Zimbabwe, as the roles it played led to increase of women and youth participation, election awareness, increase in registered eligible voters and reduced cases of political violence. Conclusion and recommendations were made on how to make the role played by ZimRights in elections to be more effective and efficient in the future elections.